Health-motivated taxes on red and processed meat: a modelling study on optimal tax levels and health and climate-change co-benefits - Springmann, Marco; Mason-D'Croz, Daniel; Robinson, Sherman; Wiebe, Keith D.; Godfray, Charles; Rayner, Mike; Scarborough, Peter (2017)
The consumption of red and processed meat has been associated with increased mortality from chronic diseases, including cancer, and its production causes a significant portion of food-related greenhouse-gas (GHG) emissions. One policy response is to regulate red and processed meat consumption similar to other foods of public health concerns. Here we describe a market-based approach of taxing red and processed meat according to its health impacts.